(untitled) (Research, Society and Development, 2020)
This article aims to contribute to the discussion about the practice as a curricular component, in the formation of future mathematics teachers, through exploratory activities developed in the discipline of Teaching Practice in Mathematics, in the Mathematics Degree. To show respect and appreciation for the informal mathematical concepts constructed by different social groups, the activities were developed involving a game, of indigenous origin. This study is qualitative, with the Design Based Research methodology. Based on the assumption that mathematics is a social production, generated by practical needs, it is expected that this area of ​​knowledge can assist in the attempt to change the educator’s posture while being responsible for providing meaningful learning for his future students. Furthermore, it is believed that the reflections produced in this text may contribute to the formation of future mathematics teachers, especially with regard to the forms of mathematical knowledge that differ from group to group, favoring the construction and reconstruction of knowledge, maintenance, substitution and modification of the ways of organizing knowledge, forming an evolutionary trajectory of the inquiring subject.